2020
DOI: 10.1109/jsen.2020.3005968
|View full text |Cite
|
Sign up to set email alerts
|

Decoding EEG Rhythms During Action Observation, Motor Imagery, and Execution for Standing and Sitting

Abstract: Event-related desynchronization and synchronization (ERD/S) and movement-related cortical potential (MRCP) play an important role in brain-computer interfaces (BCI) for lower limb rehabilitation, particularly in standing and sitting. However, little is known about the differences in the cortical activation between standing and sitting, especially how the brain's intention modulates the pre-movement sensorimotor rhythm as they do for switching movements. In this study, we aim to investigate the decoding of cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 52 publications
(53 reference statements)
1
34
1
Order By: Relevance
“…For this reason, brain computer interface (BCI) technologies based on non-invasive Electroencephalography (EEG) have been introduced to decode movement intention from brain electrical signals, even in absence of any muscular activity. Previous works have proven the feasibility of predicting motion intention with BCI to detect sit-to-stand and stand-to-sit movement (Chaisaen et al, 2020 ), to trigger lower limb exoskeletons (Kilicarslan et al, 2013 ; Lee et al, 2017 ), but also to decode walking patterns from EEG signals (Presacco et al, 2011 ; Nakagome et al, 2020 ; Tortora et al, 2020 ). However, interfaces based on EEG signals alone are not reliable enough for most clinical applications and to control advanced neurorobotics devices yet due to their low reliability, low accuracy and low informative content (Vaughan et al, 1996 ; Wolpaw et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, brain computer interface (BCI) technologies based on non-invasive Electroencephalography (EEG) have been introduced to decode movement intention from brain electrical signals, even in absence of any muscular activity. Previous works have proven the feasibility of predicting motion intention with BCI to detect sit-to-stand and stand-to-sit movement (Chaisaen et al, 2020 ), to trigger lower limb exoskeletons (Kilicarslan et al, 2013 ; Lee et al, 2017 ), but also to decode walking patterns from EEG signals (Presacco et al, 2011 ; Nakagome et al, 2020 ; Tortora et al, 2020 ). However, interfaces based on EEG signals alone are not reliable enough for most clinical applications and to control advanced neurorobotics devices yet due to their low reliability, low accuracy and low informative content (Vaughan et al, 1996 ; Wolpaw et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…A channel selection is peformed manually by selecting only three electrodes C 3 , C z and C 4 allowing to reach a mean classification accuracy beyond 71% and 70% using, respectively, the CNN-FC and the CSP with SVM algorithms. In [22], Rattanaphon et al, investigated the role of action observation and MI during the standing and sitting tasks. In this study, a fixed time window of 2s with an overlapping factor of 0.2s and 9 filter banks are used to track EEG rhythms during the sit-to-stand and stand-to-sit transitions.…”
Section: Figure 1: Typical Eeg Signal Processing Chainmentioning
confidence: 99%
“…Previous studies showed that MI and ME for hand and foot movements activate comparable brain areas, also for the execution of swallowing [23] . MI movement pattern discrimination were based on quantification of event-related synchronization/desynchronization (ERS/ERD) using bandpower (BP) [12] , [24] , which were cortical rhythms characterized by the mu and beta neural activity patterns [25] . ERD showed stronger contra-lateralization features with movement intention and execution in the sensorimotor cortices, while ERS was found prominently in the ipsilateral hemisphere [25] .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study using a simple finger-tapping task suggested that the increasing of oxyHb levels in the supplemental motor area (SMA) and premotor area (PMA) during MI were similar to those observed during ME [31] . Chaisaen et al [25] presented the decoding EEG rhythms during action observation, MI, and ME for the actions of standing and sitting.…”
Section: Introductionmentioning
confidence: 99%